Avaliação clínica dos efeitos de duas técnicas de isolamento do campo operatório no desempenho de restaurações Classe V e na condição periodontal - Fontes, Silvia Terra (2011)
During restorative procedures, different isolation methods of the operative field can be used to promote moisture control and retraction of the gingival tissues. The aim of the present clinical trial was to evaluate the effects of two isolation techniques on the clinical performance of Class V restorations, as well on the periodontal conditions of restored sites. Patients presenting at least two noncarious cervical lesions (NCLs) were enrolled in this study. The NCLs were randomized into the following groups: (1) isolation performed with rubber dam and gingival retraction clamp and (2) isolation provided with cotton rolls and gingival retraction cord. Both techniques were used with a saliva suction device. All restorative procedures were performed using a selfetching adhesive system and a nanofilled composite resin according to the manufacturer s instructions. The clinical performance of restorations was recorded in terms of fracture and retention of restoration, marginal adaptation, marginal staining, postoperative hypersensitivity, and preservation of tooth vitality at 1 week and 6 months after placement.The periodontal condition of restored sites was evaluated based on the presence of supragingival plaque, gingival marginal bleeding, probing depth, and relative gingival recession. Thirty patients were enrolled in the study, yielding a total of 136 restorations (68 restorations per group). At the 6-month followup, one restoration from the rubber dam group and three restorations from the cotton roll group lost retention. In this period, the highest incidence of small marginal defects was observed in the group isolated with cotton rolls (p= 0.01). Both groups showed a statistically significant increase in supragingival plaque at six months after restoration placement (p< 0.05). However, no significant differences were detected among the two groups tested with respect to any of the criteria used to evaluate the restorations or the periodontal condition (p> 0.05). Within the limits of this study, it can be concluded that both isolation techniques resulted in equally clinically acceptable restorations without producing negative effects on periodontal tissues